TREATMENT OF PROBLEMS IN OPIODS ABUSE - Alvárez Cerberó, Julio (Anales de Psicología / Annals of Psychology)
This article deals with the problem of drug abuse (specially heroin) from a public perspective.We make some methodological remarks, before describing the components and functioning of the two Assistential Net's main field, the drug free programs and the harm reduction ones. The article defines each one of the assistential facilities of both types of treatments, and describes the programs we kee running.However we press the idea that no a priori considerations, but only the functional analysis of behaviour can ultimately account for the individual treatment program of each drugdependent.We also highlight the strong conexion in our country between the drug problems and AIDS, and the importance therefore of prevention strategies to stop the spread of that illness.Finally we express our idea that the drug problems concern no Administration in particular, but also the NGAs and the civil society. We all must respond to give that problem a coherent solution.